The Relationship between Nutritional Status of Pregnant Women and Stunted Children - Royani, Ida; Mappaware, Nasrudin Andi; Darma, Sidrah; Khalid, Nurfadhillah; Utami, Dian Fahmi (Green Medical Journal, 2021)
Introduction: The nutritional status of pregnant women has a significant impact on the fetus's health and development. Low birth weight can be caused by womb growth problems. Research in Nepal shows that babies with low birth weight have a higher risk of becoming stunted. West Sulawesi is the most populous province in Central Indonesia, with a population of 39.7%. In Mamuju District, West Sulawesi, the relationship between stunted babies and maternal nutritional status during pregnancy was investigated. Methods: Cross sectional analytic survey with a retrospective approach. Data processing using the chi square test. The population in this study was 20.039 people. Total sampling was used to collect nutritional status data of children under the age of five in West Sulawesi province from February to June 2020. In this study, 88 people were sampled, all of whom were mothers of stunted children aged 2 to 5 Years old and who had a KIA book during pregnancy. Results: The results of statistical tests showed that the p value of nutritional status with BMI and LILA 0.000 and the p value of HB levels 0.066. There was a link between pregnant women's nutritional status and LILA, but not between HB levels and stunting. Conclusion: The conclusion of this study is that there is a relationship between the nutritional status of pregnant women based on BMI and LILA and the incidence of stunting in Mamuju Regency, West Sulawesi Province.